2018
DOI: 10.1038/s41598-018-20261-z
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing analysis revealed the regulation patterns of small RNAs on the development of A. comosus var. bracteatus leaves

Abstract: Studies of the molecular mechanisms involved in the formation of the albino leaf cells are important for understanding the development of chimera leaves in Ananas comosus var. bracteatus. In this study, we identified a total of 163 novel miRNAs involved in the development of complete white (CWh) and complete green (CGr) leaves using high-throughput sequencing method. The potential miRNA target genes were predicted and annotated using the NR, Swiss-Prot, GO, COG, KEGG, KOG and Pfam databases. The main biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…tool id=lefse upload) [39,40]. To correlate lung and intestine microbiota, analysis was performed using PICRUSt, including COG and KEGG function analysis [41,42]. The comparison between the two groups was conducted using t-test.…”
Section: Discussionmentioning
confidence: 99%
“…tool id=lefse upload) [39,40]. To correlate lung and intestine microbiota, analysis was performed using PICRUSt, including COG and KEGG function analysis [41,42]. The comparison between the two groups was conducted using t-test.…”
Section: Discussionmentioning
confidence: 99%
“…bracteatus shoots have revealed that transcriptional differences play vital roles in the biosynthesis of photosynthetic pigments and in the development of chloroplasts, which might cause differences in photosynthesis and leaf color (Li et al., 2017). miRNAs involved in the development of CGr and CWh leaves have been identified and the regulatory functions of miRNAs in albino leaf cells examined (Xiong et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…bracteatus (Fig 1A) by tissue culture, in accordance with our previous protocol [28]. Three developmental stages were evaluated based on the number of expanded leaves on the shoots [30]. WS1 (Fig 1B) and GS1 (Fig 1C) were completely white and green shoots, respectively, with only unexpanded leaves; WS2 (Fig 1D) and GS2 (Fig 1E) were completely white and green shoots, respectively, with four to five expanded leaves; WS3 (Fig 1F) and GS3 (Fig 1G) were completely white and green shoots, respectively, with ten to twelve expanded leaves.…”
Section: Methodsmentioning
confidence: 99%